Construção e ensaio de pórticos em madeira laminada colada visando emprego em aviários de postura - Stringari, Eduardo Henrique (2019)
This work aimed to evaluate the structural behavior of frames made from gluing boards of Araucaria angustifolia and polyurethane adhesive based on vegetable oils. It was tried to present an tecnical solution for the replacement of the mixed structures (reinforced concrete and metallic structure) that are constructed in the West of Paraná, to the examples of those recommended by the Cooperative Agroindustrial Lar, for execution of poultry of posture. The use of reforestation Araucaria together with the biodegradable adhesive is an alternative of sustainable construction. Five units were designed, constructed and subjected to load tests in a reduced scale in 1: 2.5, of triarticulated straight frames. They were made with a free span of 2 meters and with a slope of 15º, suitable for the use of metallic tiles, commercially known as aluzinco. Tests were carried out to characterize the wood and the adhesive, to obtain sufficient parameters for a sizing according to NBR 7190 (ABNT, 1997). The mean value obtained for the ultimate strength of the structures was 4.14 times the design load. The structures all showed satisfactory mechanical performance and deformations lower than those recommended by the standard. The adhesive based on vegetable oils showed potential for structural use. It was concluded by the technical feasibility of making frames entirely glued of lumber. This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de nível superior- Brasil (CAPES) - Finance Code 001.